Penerapan Metode Mind Mapping dalam Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMK Negeri 7 Sarolangun - Holida Holida; M. Thontawi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study is a Classroom Action Research (CAR) aimed at improving students' critical thinking skills in Islamic Religious Education at SMK Negeri 7 Sarolangun through the implementation of the Mind Mapping Method. The study was conducted in two cycles with four stages in each cycle: planning, implementation, observation, and reflection. The subjects of this study were 24 students from class X who participated in the implementation of this method. Data were collected through observation, interviews, and documentation to assess the development of students' critical thinking abilities. The results showed an improvement in critical thinking skills in each cycle. In cycle I, students' critical thinking skills reached 87.5% with an excellent category, while in cycle II, it increased to 93.57% with an excellent category. This improvement demonstrates the effectiveness of the Mind Mapping Method in helping students organize ideas, connect concepts, and analyze learning materials more systematically. Therefore, this study proves that the Mind Mapping-based learning method can be an effective alternative in improving critical thinking skills in Islamic Religious Education at SMK Negeri 7 Sarolangun. The implications of these findings highlight the importance of innovative teaching methods to support the optimal development of students' critical thinking abilities.